Prognostic selection and long-term survival analysis to assess overdiagnosis risk in lung cancer screening randomized trials. (March 2021) - Paci, Eugenio; Puliti, Donella; Carozzi, Francesca Maria; Carrozzi, Laura; Falaschi, Fabio; Pegna, Andrea Lopes; Mascalchi, Mario; Picozzi, Giulia; Pistelli, Francesco; Zappa, Marco; ,
Objectives: Overdiagnosis in low-dose computed tomography randomized screening trials varies from 0 to 67%. The National Lung Screening Trial (extended follow-up) and ITALUNG (Italian Lung Cancer Screening Trial) have reported cumulative incidence estimates at long-term follow-up showing low or no overdiagnosis. The Danish Lung Cancer Screening Trial attributed the high overdiagnosis estimate to a likely selection for risk of the active arm. Here, we applied a method already used in benefit and overdiagnosis assessments to compute the long-term survival rates in the ITALUNG arms in order to confirm incidence-excess method assessment. Methods: Subjects in the active arm were invited for four screening rounds, while controls were in usual care. Follow-up was extended to 11.3 years. Kaplan-Meyer 5- and 10-year survivals of "resected and early" (stage I or II and resected) and "unresected or late" (stage III or IV or not resected or unclassified) lung cancer cases were compared between arms. Results: The updated ITALUNG control arm cumulative incidence rate was lower than in the active arm, but this was not statistically significant (RR: 0.89; 95% CI: 0.67–1.18). A compensatory drop of late cases was observed after baseline screening. The proportion of "resected and early" cases was 38% and 19%, in the active and control arms, respectively. The 10-year survival rates were 64% and 60% in the active and control arms, respectively ( p  = 0.689). The five-year survival rates for "unresected or late" cases were 10% and 7% in the active and control arms, respectively ( p  = 0.679). Conclusions: This long-term survival analysis, by prognostic categories, concluded against the long-term risk of overdiagnosis and contributed to revealing how screening works.